2021
DOI: 10.20473/imhsj.v5i4.2021.333-339
|View full text |Cite
|
Sign up to set email alerts
|

Description of the Level of Anxiety in Post Partum

Abstract: Background: The puerperium begins when the baby and placenta are born until the uterus returns to its pre-pregnancy state, and generally lasts for 6 weeks. There are several adaptations that must be passed by postpartum  period including physiological, psychological and social. Anxiety is part of the psychological disorders of postpartum mothers, if anxiety is not handled it can cause postpartum blues and its impact causes a decrease in children's cognitive abilities compared to their peers. The purpose of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
4
0
7
Order By: Relevance
“…Based on the study's results, it was found that the patient data of Mrs. F is 17 years old, and that age is classified as a teenager. Alfya Lailatul Istiqomah (2021) explained that age during pregnancy affects a mother's ability to accept responsibilities (Istiqomah, Viandika and Khoirun Nisa, 2021). This is in line with the results; pregnancy at an immature age can cause fear during pregnancy and childbirth, as well as during puerperium, due to the immaturity of t he reproductive organs and not being ready to become a mother.…”
Section: Assessment Analysismentioning
confidence: 58%
See 2 more Smart Citations
“…Based on the study's results, it was found that the patient data of Mrs. F is 17 years old, and that age is classified as a teenager. Alfya Lailatul Istiqomah (2021) explained that age during pregnancy affects a mother's ability to accept responsibilities (Istiqomah, Viandika and Khoirun Nisa, 2021). This is in line with the results; pregnancy at an immature age can cause fear during pregnancy and childbirth, as well as during puerperium, due to the immaturity of t he reproductive organs and not being ready to become a mother.…”
Section: Assessment Analysismentioning
confidence: 58%
“…The level of anxiety that occurs in primiparous mothers reaches 83.4% for severe anxiety and 16.6% for moderate anxiety. Meanwhile, the incidence of anxiety in multiparous mothers reached 7% for severe anxiety, 71.5% for moderate anxiety and 21.5% for mild anxiety (Istiqomah, 2021).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Dol et al, determined that social support was negatively associated with postpartum depressive symptoms and anxiety symptoms 46 . A previous study indicated that postpartum anxiety can arise in mothers due to various factors; therefore, comprehensive support and care are needed in the postpartum maternal adaptation process 47 . In the literature and in this research, it is seen that the presence of postpartum anxiety in the mother negatively affects maternal psychology, self-care of the baby and mother, social support and adaptation to motherhood, making it difficult for the mother to adapt to the postpartum process.…”
Section: Discussionmentioning
confidence: 99%
“…Masa nifas adalah masa yang terbentuk setelah presentasi diberikan dan setelah alat-alat kandungan berlangsung, termasuk keadaan setelah hamil yang telah berlangsung selama 6 minggu atau 42 hari. 1 Ibu nifas kesehatan adalah proses yang berlangsung secara standar dan dilakukan secara berurutan selama dua bulan kalender, yaitu pada hari ke-6 dan ke-4 dengan 3 persalinan, pada hari ke-4 dan ke-4 dengan 28 persalinan, dan pada hari ke-29 dan ke-29 dengan 42 persalinan. 2 Menurut Survei Demografi Kesehatan Indonesia 2018, Angka Kematian Ibu (AKI) adalah 359 per 100,000 hidup.…”
Section: Pendahuluanunclassified